Demographic features, clinical characteristics, and comorbid relation in hidradenitis suppurativa: a population-based study - Kaya, Gökhan; Özgen, Fatma Pelin; Kelahmetoğlu, Osman; Su Küçük, Özlem; Onsun, Nahide (Frontiers in Medicine, 2025)
Background/objectiveHidradenitis suppurativa (HS) is a chronic inflammatory disease affecting apocrine gland areas, characterized by painful nodules and abscesses that may result in sinus tracts and scarring. The global prevalence of HS is increasing due to heightened awareness, improved diagnostic methods, rising obesity rates, and higher smoking prevalence. This study aimed to describe the epidemiological, clinical, and comorbid characteristics of HS patients.MethodologyThis retrospective descriptive cross-sectional study included 193 outpatients aged between 15 and 73 years who visited a tertiary HS clinic between 2017 and 2022. Demographic, clinical, and comorbid characteristics were recorded and analyzed using chi-square and ordinal regression methods.ResultsThe mean age was 34.5 ± 12.1 years, with a mean disease duration of 5.9 ± 6.7 years. According to the Hurley classification, 61.1, 24.4, and 14.5% were stages I, II, and III, respectively. Comorbidities were present in 48.2% of patients, with psychiatric disorders (19.2%), diabetes mellitus (14%), and hypertension (9.3%) being most common. Disease duration, smoking, male gender, and atypical localization were associated with increased disease severity.ConclusionGeographic and cultural factors influence the prevalence, severity, and management of HS, necessitating tailored treatment. Effective management requires multidisciplinary screening for early detection and prevention of comorbidities, including psychiatric disorders, cardiovascular conditions, and metabolic syndrome.